2017
DOI: 10.1038/srep43517
|View full text |Cite
|
Sign up to set email alerts
|

WEE1 inhibition targets cell cycle checkpoints for triple negative breast cancers to overcome cisplatin resistance

Abstract: Cisplatin is one of the most commonly used therapeutic drugs for cancer therapy, yet prolonged cisplatin treatment frequently results in drug resistance. To enhance therapeutic effect of cisplatin, we conducted a high throughput screening using a kinase library containing 704 kinases against triple negative breast cancer (TNBC) cells. We demonstrated that cisplatin activates ATR, CHK1 and WEE1, which shut down DNA replication and attenuate cisplatin induced-lethality. WEE1 inhibition sensitizes TNBCs and cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 54 publications
(99 reference statements)
4
35
0
Order By: Relevance
“…Our loss-of-function genetic screen allowed showing that the kinase ATR is, at least in part, responsible of this resistance, and suggests that the ATRi and oxaliplatin combination therapy could be useful in the clinic. Similar screenings have already demonstrated that ATR, CHK1, and WEE1 are involved in the sensitivity to cisplatin in triplenegative breast cancer (36). Moreover, ATR inhibition sensitized cancer cells to chemotherapy, for instance in ovarian cancer (in combination with cisplatin and gemcitabine), in pancreatic cancer (with gemcitabine), in breast cancer (with camptothecin) and in lung cancer (with cisplatin, oxaliplatin, gemcitabine, etoposide, and SN38; ref.…”
Section: Discussionsupporting
confidence: 63%
“…Our loss-of-function genetic screen allowed showing that the kinase ATR is, at least in part, responsible of this resistance, and suggests that the ATRi and oxaliplatin combination therapy could be useful in the clinic. Similar screenings have already demonstrated that ATR, CHK1, and WEE1 are involved in the sensitivity to cisplatin in triplenegative breast cancer (36). Moreover, ATR inhibition sensitized cancer cells to chemotherapy, for instance in ovarian cancer (in combination with cisplatin and gemcitabine), in pancreatic cancer (with gemcitabine), in breast cancer (with camptothecin) and in lung cancer (with cisplatin, oxaliplatin, gemcitabine, etoposide, and SN38; ref.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies have reported the sensitivity of TNBC to WEE1 targeting in the presence of either PARP or ATR inhibitors, or Cisplatin. [17,19,20,22,41] However, we found that MMTV-R26 Met MGT cells were either resistant or only partially sensitive to these drug combinations ( Figure 5E), recapitulating other mechanisms of primary resistance beside those reported in Figure 3G-H. Thus, BCL-XL targeting is a preferable strategy to exacerbate WEE1 essentiality in TNBC.…”
Section: Combined Targeting Of Wee1 and Bcl-xl Is Deleterious For Tnbmentioning
confidence: 63%
“…Co-inhibition of WEE1 with either radiotherapy or anticancer drugs such as cisplatin, gemcitabin, paclitaxel, or inhibitors of CDC25, ATR, or PARP causes death of breast cancer cells. [15][16][17][18][19][20][21][22] The rational of these combined treatments is to associate DNA-damaging therapies together with perturbation of DNA damage checkpoint gatekeepers through WEE1 targeting. Nevertheless, the consequences of WEE1 targeting may be broader than cell cycle regulation, in view of recent studies showing that WEE1 inactivation increases CDK-dependent firing of dormant replication origins thereby leading to replication stress and increased dNTP demand.…”
Section: Introductionmentioning
confidence: 99%
“…In triple-negative breast cancer, WEE1 inhibition overcame cisplatin resistance by disrupting DNA replication and G2/ M cell cycle checkpoint regulation [20]. A clinical trial also revealed that BTC patients harboring DDR-related gene mutations responded better to cisplatin therapy than those with wild-type cancer [21].…”
Section: Discussionmentioning
confidence: 99%